What might melatonin supplementation provide for humans beyond improved onset to sleep? - Leticia A. Shea (Exploration of Neuroscience)
Melatonin is widely available as a dietary supplement and/or medicine for sleep. It is an endogenous hormone produced in the pineal gland of the brain, with metabolites providing additional beneficial mechanisms such as supporting long-term memory. Melatonin is well known as a hormone that plays a role in the circadian rhythm (sleep cycle), but additional mechanisms such as antioxidant, and anti-inflammatory activity are elucidated from animal research models. This article discusses melatonin supplementation and the current understanding of how it may provide benefits beyond the use as a sleep aid including a review of the evidence in how it may aid in mitigating components of cognitive decline.